Overexpression of LIMK1 in hippocampal excitatory neurons improves synaptic plasticity and social recognition memory in APP/PS1 mice - Zhang, Haiwang (Mol Brain, 2021)
Accumulating evidence indicates that the actin regulator cofilin is overactivated in Alzheimer’s Disease (AD), but whether this abnormality contributes to synaptic and cognitive impairments in AD is unclear. In addition, the brain region and cell types involved remain unknown. In this study, we specifically manipulate LIMK1, the key protein kinase that phosphorylates and inactivates cofilin, in the hippocampus of APP/PS1 transgenic mice. Using local injections of the AAV virus containing LIMK1 under the control of the CaMKIIα promoter, we show that expression of LIMK1 in hippocampal excitatory neurons increases cofilin phosphorylation (i.e., decreases cofilin activity), rescues impairments in long-term potentiation, and improves social memory in APP/PS1 mice. Our results suggest that deficits in LIMK1/cofilin signaling in the hippocampal excitatory neurons contribute to AD pathology and that manipulations of LIMK1/cofilin activity provide a potential therapeutic strategy to treat AD. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13041-021-00833-3.